A Potential Dubin-Johnson Syndrome Imaging Agent: Synthesis, Biodistribution, and MicroPET Imaging - Jeongsoo Yoo; David E. Reichert; Joonyoung Kim; Carolyn J. Anderson; Michael J. Welch (Molecular Imaging)
Dubin-Johnson syndrome (DJS) is caused by a deficiency of the human canalicular multispecific organic anion transporter (cMOAT). A new lipophilic copper-64 complex of 1,4,7-tris(carboxymethyl)-10-(tetradecyl)-1,4,7,10-tetraazadodecane (5) was prepared and evaluated for potential as a diagnostic tool for DJS. The prepared ligand was labeled with 64 Cu citrate in high radiochemical purity. In vivo uptake and clearance of the complex was determined through biodistribution studies using normal Sprague-Dawley rats and mutant cMOAT-deficient (TR − ) rats. In normal rats, the radioactive copper complex was cleared quickly from the body exclusively through the hepatic pathway. The 64 Cu complex was taken up rapidly by the liver and quickly excreted into the small intestine and then the upper large intestine, whereas < 1% ID/organ was found in the kidney at all time points post injection. Whereas activity was accumulated continuously in the liver of TR − rats, it was not excreted into the small intestine. MicroPET studies of normal and TR rats were consistent with biodistribution data and showed dramatically different images. This study strongly suggests that cMOAT is involved in excretion of 64 Cu-5. The significant difference between the biodistribution data and microPET images of the normal and TR − rats demonstrates that this new 64 Cu complex may allow noninvasive diagnosis of DJS in humans.